2007
DOI: 10.1080/14017430601164263
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of interleukin-6 and matrix metalloproteinase-9 are of cardiac origin in acute coronary syndrome

Abstract: Elevated levels of IL-6, hs-CRP and MMP-9 provide a link between inflammation, matrix degradation and the development and progression of ACS. IL-6 and MMP-9 appear to be released mainly from vulnerable plaque or necrotic myocardium during the acute phase of MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
0
20
0
6
Order By: Relevance
“…According to the available literatures, this phenomenon cannot be explained successfully. Other than the role as an inflammatory mediator in the myocardial ischemia-reperfusion process [24,25], we speculate that IL-6 may also be an inflammatory marker [26]. That is, appearance of IL-6 in the serum may reflect existence and severity of the inflammatory state.…”
Section: Discussionmentioning
confidence: 98%
“…According to the available literatures, this phenomenon cannot be explained successfully. Other than the role as an inflammatory mediator in the myocardial ischemia-reperfusion process [24,25], we speculate that IL-6 may also be an inflammatory marker [26]. That is, appearance of IL-6 in the serum may reflect existence and severity of the inflammatory state.…”
Section: Discussionmentioning
confidence: 98%
“…124 As IL-6 is the primary cytokine of the inflammatory process 126 and inflammatory plaque destabilisation is key to plaque rupture, it has been suggested that IL-6 measurement may be useful in patients with ACS. IL-6 has been shown to be of cardiac origin in ACS 127 and to relate to other risk factors. 128 Studies have shown that IL-6 measurement is prognostic in patients with ACS, 129-131 but data are not consistent.…”
Section: Interleukinmentioning
confidence: 99%
“…The myocardium is critical for the production of several inflammatory cytokines during reperfusion injury as a mechanism to start tissue repair, but it also becomes a target of their cytotoxic effects (26). For example, in patients with myocardial infarction IL-6 appears to be synthesized in the myocardium during the ischemic period and its secretion is further triggered by the reperfusion process (27, 28). Increased IL-6 is associated with poor prognosis in patients with myocardial infarction or heart failure (29) and with life-threatening events, such as shock, decreased myocardial contractility and arrhythmias (30, 31).…”
Section: Discussionmentioning
confidence: 99%